Intellectual property protection lost and competition: An examination using large language models - Acikalin, Utku U.; Caskurlu, Tolga; Hoberg, Gerard; Phillips, Gordon M. (Journal of Financial Economics, 2026)
We examine the impact of lost intellectual property protection on innovation, competition, firm performance, and valuation. We consider firms whose ability to protect intellectual property (IP) using patents is weakened following a major Supreme Court decision. We use large language models (LLM) to identify firms’ patent portfolios’ exposure to this decision and find an unequal impact. Large firms gain and small firms lose. Large impacted firms benefit as their sales growth increases and their exposure to lawsuits decreases. Small impacted firms lose as they face increased competition, product-market encroachment, and lower profits and valuations. They increase R&D and nondisclosure agreements.